Tumor-Associated Fibroblasts and their Matrix Tumor Stroma - Mueller, Margareta M.; Fusenig, Norbert E.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
During the last 20 years it has become increasingly clear that the tumor micro-environment, the tumor stroma with its cellular end extracellular components, plays an crucial role in regulating tumor growth and progression. This book on (3z(BTumor-associated fibroblasts and their matrix(3y (Bas part of the series on (3z(BTumor-Microenvironment(3y (Bis the first comprehensive discussion of these two main players of the tumor microenvironment. The best experts in this new area of tumor research and therapy review the role of these major components in the tumor stroma in the process of tumor development and progression. They discuss their interaction with other players such as blood vessels and immune cells, and show novel perspectives for tumor therapy. This compilation of excellent contributions of the best known experts in this important field in cancer research and therapy is a must for all scientists engaged in basic and clinical research. Increasing evidence of successful targeting of both cellular and matrix components in tumor therapy renders this book of particular interest for scientists engaged in pharmaceutical industry searching for new components for cancer therapy.s
Keywords: Medicine; Oncology; Biomedicine; Cancer Research; Biomedicine general; Oncology